Production of palm oil-based fatty acid methyl ester (FAME) a plant design - Aligato, Albert Daniel E.; Labor, Francis Gerald P.; Moldez, Ruel Jan Anthony A.; Rosales, Marc Francis R.; Dela Cruz, John Von Wernher C. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
With the pending increase of biodiesel blends from 2% to 10% in 2020, to a further 20% in 2030 in the Philippines, there is a need for more fatty acid methyl ester (FAME) producers in the country. Current producers of FAME only rely on coconut oil, a relatively expensive resource, for raw materials. This study was done to design a FAME production plant that proved to be technically and economically feasible, while using palm oil as an alternative raw material to produce FAME. The supercritical Saka-Dadan Method was chosen as the method of FAME production due to its higher conversion and the lack of the undesirable saponification side reaction. This allows for more products and desirable byproducts to be produced and, along with raw material recovery and recycling, allows for the minimization of required separation process and waste production. Equipment sizing was done to allow the production of at least 20% of the deficit to the impending blend increase due by 2020. Pipe sizing was optimized such that pipes were not too large to be too costly yet were also not too small to cause significant friction losses. Rotating equipment design ensured head and flow rate requirements were met without the risk of cavitation in pumps and overheating in compressors. Reactor design guaranteed a high conversion rate with an optimized volume. Heating jackets were installed to retain an isothermal condition, and temperature alarms for low and low-low conditions were installed to ensure the temperatures in the reactors remain at the required range. Due to the high energy requirements of the process, a heat exchanger network was employed to recover and reuse energy from the system. This resulted to a system composed of 27 heat exchangers, most of which utilize process streams as heating or cooling fluids. It was found that annually, utility consumption would amount to 94.2 million USD, and annual raw material costs would total 198.2 million USD, accounting for 67.74% of the operating costs. The total cost of equipment was found to be 74 million USD, 60.62% of which would solely be for the numerous heat exchangers. The product and byproduct would however net a total of 358.8 million USD annually, with the FAME product accounting for 97.84% of the sales. Assuming a two-year construction period financed with 40% equity and 60% bank loan resulted to a net present value of 219 million USD, and a discounted payback of 6 years. The internal rate of return was found to be 24%, well within the 16-24% minimum acceptable rate of return for plants utilizing a new process to produce a product already in the market.
Submitted in partial fulfillment of the requirements in ChE 142 Chemical Engineering Plant Design.
Keywords: Chemical plants -- Design and construction; Fatty acid methyl esters (FAME).